Protection from Hg-Inactivation of Factor XIII by Mercaptalbumin - Fantl, P (Thrombosis and Haemostasis, 1970)
The blood plasma factor XIII (fibrin stabilizing factor) is inactivated by mercuric ions and can be reactivated by serum - or plasma albumin of which the active component is mercaptalbumin. A relation between mercaptalbumin concentration and factor XIII activity is pointed out.